Process development in Hansenula polymorpha and Arxula adeninivorans, a re-assessment - Stöckmann Christoph; Scheidle Marco; Dittrich Barbara; Merckelbach Armin; Hehmann Grit; Melmer Georg; Klee Doris; Büchs Jochen; Kang Hyun Ah; Gellissen Gerd (Microbial Cell Factories, 2009)
Abstract A range of industrial H. polymorpha-based processes exist, most of them for the production of pharmaceuticals. The established industrial processes lean on the use of promoters derived from MOX and FMD, genes of the methanol metabolism pathway. In Hansenula polymorpha these promoters are de-repressed upon depletion of a range of carbon sources like glucose and glycerol instead of being induced by methanol as reported for other methylotrophs. Due to these characteristics screening and fermentation modes have been defined for strains harbouring such expression control elements that lean on a limited supplementation of glycerol or glucose to a culture medium. For fermentation of H. polymorpha a synthetic minimal medium (SYN6) has been developed. No industrial processes have been developed so far based on Arxula adeninivorans and only a limited range of strong promoter elements exists, suitable for heterologous gene expression. SYN6 originally designed for H. polymorpha provided a suitable basis for the initial definition of fermentation conditions for this dimorphic yeast. Characteristics like osmo- and thermotolerance can be addressed for the definition of culture conditions.